2016
DOI: 10.1186/s13039-016-0251-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel de novo microdeletion at 17q11.2 adjacent to NF1 gene associated with developmental delay, short stature, microcephaly and dysmorphic features

Abstract: BackgroundMicrodeletions at 17q11.2 often encompass NF1 gene, is the cause for NF1 microdeletion syndrome. Microdeletion at 17q11.2 without the involvement of NF1 gene is rarely reported.Case presentationHere we reported a patient carrying a novel de novo deletion at 17q11.2 adjacent to NF1 gene, who presented with developmental delay, short stature, postnatal microcephaly, underweight and dysmorphic features including flat facial profile, dolicocephaly, hypertelorism, short philtrum, flat nasal bridge and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…It is not surprising that patients with mutations in the NF1 gene can also present with features overlapping with those seen in NS patients, considering that both the NF1 gene and the NS genes express proteins which are integral components of the RAS‐MAPK developmental pathways during embryogenesis . Also, the complete loss of one of the alleles of the NF1 gene is the probable cause of the relatively more severe and earlier presentation of cognitive abnormalities and dysmorphism in our patient, a phenomenon also observed in previous reports of NF1 microdeletions …”
Section: Short Reportsupporting
confidence: 84%
See 1 more Smart Citation
“…It is not surprising that patients with mutations in the NF1 gene can also present with features overlapping with those seen in NS patients, considering that both the NF1 gene and the NS genes express proteins which are integral components of the RAS‐MAPK developmental pathways during embryogenesis . Also, the complete loss of one of the alleles of the NF1 gene is the probable cause of the relatively more severe and earlier presentation of cognitive abnormalities and dysmorphism in our patient, a phenomenon also observed in previous reports of NF1 microdeletions …”
Section: Short Reportsupporting
confidence: 84%
“…4 Also, the complete loss of one of the alleles of the NF1 gene is the probable cause of the relatively more severe and earlier presentation of cognitive abnormalities and dysmorphism in our patient, a phenomenon also observed in previous reports of NF1 microdeletions. [5][6][7][8][9] Although SNP analysis using array CGH indicated that the microdeleted allele was maternal in origin, no genomic abnormality was detected in either parent. Hence, we concluded that this 1.7 Mb microdeletion within the 17q11.2 region probably occurred as a de novo event.…”
Section: Nf1 Phenotypementioning
confidence: 99%
“…17q11.2 microdeletions, encompassing NF1 gene, are responsible for NF1 microdeletion syndrome [5], which include dysmorphic features, neurodevelopmental delay, cardiovascular defects, overgrowth, a higher tumor burden and earlier onset of benign neurofibromas and malignant peripheral nerve sheath tumors (MPNST)/other malignancies [2]. It represents 4.2% of all NF1 patients.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the likely effect of the deleted genes, the probability of loss-of-function (LoF) intolerance should be considered, differentiating genes in LoF intolerant or tolerant [2]. Specifically, 5 genes ( CRLF3 , ATAD5 , RAB11FIP4 , SUZ12 and LRRC37B ) were predicted to be LoF intolerant [2], which means that they could have clinical consequences if present in one copy [5]; 4 of them (2 partially) are deleted in our subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A microdeletion on chromosome 17, comprising TAOK1, had nominated TAOK1 as a potential candidate gene for developmental delay and microcephaly. 26 The Decipher database reports four additional patients with large deletions that include the TAOK1 gene. These patients include one who has an intragenic deletion of exons 2-8 and a reported phenotype of microcephaly and seizures.…”
mentioning
confidence: 99%